2017
DOI: 10.3389/fpsyg.2017.01896
|View full text |Cite
|
Sign up to set email alerts
|

Can Limitations of Visuospatial Attention Be Circumvented? A Review

Abstract: In daily life, humans are bombarded with visual input. Yet, their attentional capacities for processing this input are severely limited. Several studies have investigated factors that influence these attentional limitations and have identified methods to circumvent them. Here, we provide a review of these findings. We first review studies that have demonstrated limitations of visuospatial attention and investigated physiological correlates of these limitations. We then review studies in multisensory research t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 110 publications
0
11
1
Order By: Relevance
“…For navigational tasks, acquiring spatial knowledge is crucial to orient and navigate in space without losing the way (Montello, 2005; Siegel & White, 1975). However, the formation of mental spatial representations is demanding and limited by humans’ attentional capacities (Downs & Stea, 1973; Münzer et al, 2006; Siegel & White, 1975; Wahn & König, 2017; Weisberg & Newcombe, 2018). Therefore, we often use a navigational aid to support the cognitive processes required to navigate as optimally as possible in an unknown environment (Ludwig, Müller, & Ohm, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For navigational tasks, acquiring spatial knowledge is crucial to orient and navigate in space without losing the way (Montello, 2005; Siegel & White, 1975). However, the formation of mental spatial representations is demanding and limited by humans’ attentional capacities (Downs & Stea, 1973; Münzer et al, 2006; Siegel & White, 1975; Wahn & König, 2017; Weisberg & Newcombe, 2018). Therefore, we often use a navigational aid to support the cognitive processes required to navigate as optimally as possible in an unknown environment (Ludwig, Müller, & Ohm, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Participants performed the visual search task faster when receiving the viewing information via the tactile or auditory modalities as compared to the visual sensory modality. This multisensory benefit has been explained by the larger availability of attentional resources across sensory modalities compared to within one sensory modality . These results suggest that an already existing collective benefit in joint visuospatial tasks can be enhanced by exchanging information between coactors via other sensory modalities than vision.…”
Section: Joint Visuospatial Tasksmentioning
confidence: 81%
“…Besides these directions for future research, there are also a number of applications of group benefits research. In particular, studying group benefits in joint perceptual tasks has the potential to circumvent processing limitations within individuals and thereby reduce the risk of errors and accidents. For instance, research on visual search showed that humans perform poorly on searches, in which the prevalence of targets is low .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies show that responding jointly reduces the interference of competing stimuli in a multisensory setting (Wahn & König, 2017 ). The results seem at odds with a recent tradition of research showing that acting jointly increases the interference of irrelevant stimuli, presumably due participants co-representing each other’s tasks besides their own (Sebanz, Knoblich, & Prinz, 2003 , 2005 ).…”
Section: Non-visual Senses Enhance Visual Joint Attentionmentioning
confidence: 99%